The Design of Condensate Measurement for Balanced Ambient Room-type Calorimeter - Liu Shengyao; Li Ying; Huang Caifeng; Zhao Sihai (Zhileng xuebao)
During the cooling capacity measurement of small and medium size air conditioner, the indoor cooling capacity calculation formula of room-type calorimeter didn’t take the dehumidification of air handling cabinet into consideration. In order to eliminate the impact of this influence on the test results, the mass weighing method was proposed to measure the humidification water of inner and outer chamber of the calorimeter, as well as the condensate water of air conditioner under test respectively. By analyzing the two sets of test results of five test units which were tested by means of room-type calorimeter based on the mass weighing method: It turns out that, when the rated cooling capacity of the air conditioner under test is smaller than the input power of the test chamber, the test error is increased by the air handling cabinet’s dehumidification amount, and the test error arises with the decrease of cooling capacity of air conditioner. The indoor cooling capacity calculation formula is modified to improve its accuracy according to the test results.